(3GdeTjNI GdHZOGOjIs - (3GdSdaj , CMeO Hf eMeO Hf Sdag GdCUHgGfj, UOQ GdOjf CHh WGgQ,J (B576 (3g` s
(3ChdgG (B:s
(3JHJOF HMOjK (B" (3djS Ydi Cgd dG Edg EdG Gddg hMTI ai bHhQge (B" s
(3fSNI KGfjI Yf fSNI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B75s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B249 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs